IoT and HPC Integration: Revision and Perspectives - Cimino, Leonardo de Souza; Resende, José Estevão Eugênio de; Silva, Lucas Henrique Moreira; Rocha, Samuel Queiroz Souza; Correia, Matheus de Oliveira; Monteiro, Guilherme Souza; Fernandes, Gabriel Natã de Souza; Almeida, Silvia Grasiella Moreira; Almeida, André Luiz Barroso; Aquino, André Luiz Lins de; Lima, Joubert de Castro (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2017)
In this paper, we review the main middleware re-quirements applied to Internet of Things and High-Performance Computing combined, here called IoT/HPC. The goal was to describe a unique set of requirements that middleware systems should attempt to guarantee the development of integrated applications. Among many core complex services, the IoT/HPC challenges are related to the support of sensing, actuating, storage and processing services combined in a single middleware alternative. We evaluated a set of Java solutions which were classified separately into three types: Internet of Things, High-Performance Computing and Cloud of Things. We also compared them following the same IoT/HPC requirements. The conclusion is that there is still a substantial gap in the integration of Internet of Things and High-Performance Computing and vice-versa in the middleware literature, but there are user applications that require this integration; thus, a middleware proposal project becomes fundamental for simplifying such development.